Study of interplay between magnetic/electric fields and Cr-doped effect in Mo1-xCrxSe2 (x=0, 0.5) nanosheet - Lee, Yu-Ting; Tsai, Tung-Chi; Yang, Chun-Chuen; Tung, Yung-Hsiang; Lin, Kuen-Song (2023 IEEE International Magnetic Conference - Short Papers (INTERMAG Short Papers), 2023)
The Cr-doped effects on 2D MoSe 2 nanosheet and the interplay between external magnetic and electric fields are studied. The MoSe 2 changes its magnetism from diamagnetism to paramagnetism as Cr ions substitute the Mo ones. Vacancies at the Mo site in pure MoSe 2 also result in the paramagnetism below 10 K. A 1g mode of Raman spectra display two at characteristic temperatures, 150 K (T a ) and 210 (T b ) for x=0, and 180 K (T a ') and 260 K (T b ') for x=0.5. All of the anomalies disappear as an external magnetic field is applied. This observation implies that the two abnormalities at A 1g mode correlated to the magnetic fields but were irreverent to the interplane distance. A similar effect does not find when an external electric field is subject to the Cr-doped sample, but the peak width of pure MoSe 2 will gradually broaden as the external electric field increases and will not narrow down again as removed the field. These observations imply that the smaller Cr ions reduce the interplane distance and enhance the coupling strength along the c-axis. This effect resists the influence of an external electric field and increases the characteristic temperatures in A 1g mode.